Paving composition and preparation method thereof
By using low molecular weight polyolefins and glycidyl-based compounds as performance enhancement additives in asphalt binders, combined with recycled plastics, the problem of poor storage stability of asphalt binders is solved, and efficient application and cost reduction of recycled plastics is achieved.
Patent Information
- Application Number
- CN202380059674.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-11
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the asphalt binder containing recycled polyethylene has poor storage stability, which limits the application of recycled plastic in asphalt.
Low molecular weight polyolefins and glycidyl compound are used as performance enhancement additives, combined with recycled plastics to form a stable bituminous binder.
It improves the storage stability of asphalt binder, increases the concentration of recycled plastic, reduces the asphalt content, reduces the cost, and improves the mechanical strength.
Smart Images

Figure CN119731135A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to paving compositions and methods of making the same. More particularly, the paving compositions include asphalt and recycled plastic, wherein a performance enhancing additive facilitates the incorporation of the recycled plastic into the paving composition. Background Art
[0002] In 2015, the United States generated 34,500,000 tons of waste plastics, and 9.1% of that waste plastics was recycled. In 2018, the United States generated 38,500,000 tons of waste plastics, and 4.4% of that waste plastics was recycled. The projected figure for 2019 is 40,000,000 tons of waste plastics, with a recycling rate of 2.9%. The Plastics Industry Association is working to identify end markets for recycled plastics. Their market research report states that the U.S. asphalt market is large enough to absorb all of the recyclable polyethylene film in the United States. One of the main challenges of recycling polyethylene film in asphalt binders used in asphalt is the poor storage stability of asphalt binders containing recycled polyethylene. This poor storage stability significantly limits the application of recycled plastics in asphalt.
[0003] Therefore, it is desirable to find materials and methods to improve the storage stability of asphalt binders containing recycled waste polyethylene. In addition, it is desirable to find materials and methods for incorporating waste plastics into asphalt compositions. In addition, with this background, other desirable features and characteristics of the present embodiments will become apparent from the subsequent detailed description and the appended claims. Summary of the invention
[0004] The present invention provides a paving composition and a method for preparing the same. In an exemplary embodiment, the paving composition comprises a binder, wherein the binder comprises asphalt, recycled plastic, and a performance enhancing additive. The performance enhancing additive is selected from the group consisting of a low molecular weight polyolefin, a glycidyl compound, and a combination thereof. The low molecular weight polyolefin has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. The glycidyl compound comprises an ethylene (meth) acrylate glycidyl ester polymer having a weight average molecular weight of about 500 Daltons to about 30,000 Daltons.
[0005] In another embodiment, a method for preparing a paving composition is provided. The method includes preparing a binder comprising asphalt, a performance enhancing additive, and recycled plastic. The performance enhancing additive is melted into the binder and is selected from the group of low molecular weight polyolefins, glycidyl compounds, and combinations thereof. The low molecular weight polyolefin has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. The glycidyl compound comprises an ethylene (meth) acrylate glycidyl polymer having a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. The recycled plastic is also melted into the binder. The binder is mixed with an aggregate to prepare the paving composition, wherein the aggregate is a solid material that can be distinguished from the binder by detection.
[0006] In another embodiment, another paving composition is provided. The paving composition comprises a binder, an aggregate, and a performance enhancing additive. The binder is present in an amount of about 1% to about 15% by weight based on the total weight of the paving composition and comprises asphalt. The aggregate is present in an amount of about 85% to 99% by weight, wherein the aggregate is a solid material that can be distinguished from the binder by detection. Based on the total weight of the aggregate, the aggregate comprises about 1% to 100% by weight of waste plastic. The performance enhancing additive is selected from the group of low molecular weight polyolefins, glycidyl compounds, and combinations thereof. The low molecular weight polyolefin has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, wherein the glycidyl compound comprises ethylene (meth) acrylate glycidyl ester polymer, and wherein the ethylene (meth) acrylate glycidyl ester polymer has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] The present embodiment will be described hereinafter in conjunction with the following drawings, and wherein:
[0008] Figures 1 to 4 is a photograph of an aggregate with an asphalt covering, where Figure 1 and Figure 2 Comprising 100% asphalt, Figure 3 and Figure 4 Comprises 97% bitumen and 3% low molecular weight oxidized polyethylene. DETAILED DESCRIPTION
[0009] The following detailed description is merely exemplary in nature and is not intended to limit the various embodiments or applications and uses of the embodiments described herein. Furthermore, it is not intended to be bound by any express or implied theory presented in the preceding technical field, background technology, summary of the invention or the following detailed description.
[0010] Generally speaking, recycled plastics can be included in asphalt compositions in two different ways. In one way, recycled plastics are melted into a molten binder and become part of the binder. This is referred to as a "wet" method in this article, and the recycled plastics used in the wet method are referred to as "recycled plastics". Alternatively, waste plastics are added to the asphalt composition as a solid, wherein the binder flows around the waste plastics, but does not significantly melt the waste plastics, so that the granular waste plastics remain separately identifiable with the binder in the asphalt composition. This is referred to as a "dry" method in this article, and the recycled plastics used in the dry method are referred to as "waste plastics" in this article to distinguish the uses of recycled plastics. Both wet and dry methods can also be used simultaneously. Both recycled plastics and waste plastics are recycled plastics or factory waste that have previously been used, such as by consumers or used in industry. After use, recycled plastics are recovered for reuse and recycling. In some embodiments, recycled plastics can be washed and / or classified before reuse. As used herein, "asphalt composition" is a general term for a composition comprising asphalt.
[0011] A technique for increasing the storage stability of an asphalt composition comprising recycled plastics is provided. The recycled plastics may be included in a wet process, a dry process, or both. In the wet process, asphalt and recycled plastics are melted together to form a binder, wherein a performance enhancing additive is used to increase the storage stability of the binder. The performance enhancing additive also provides other benefits, such as increasing the PG grade of the paving composition, easier compaction, reducing the asphalt content to reduce costs, and higher mechanical strength when compared to comparable compositions that do not contain the performance enhancing additive.
[0012] The performance enhancing additive is selected from one or both of two components: (1) a low molecular weight polyolefin having a weight average molecular weight of about 500 Daltons to about 30,000 Daltons; and (2) a glycidyl compound, wherein the glycidyl compound comprises an ethylene (meth) acrylate glycidyl polymer having a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. The performance enhancing additive allows for higher concentrations of recycled plastics to be incorporated into the binder and also increases the stability of the binder with the recycled plastics. The waste plastic is used as a component of the aggregate or as the entirety of the aggregate in a dry process, wherein the binder is added to the solid aggregate to form an asphalt composition. The performance enhancing additive increases the density of the asphalt composition due to greater compaction and fewer and / or smaller air voids. The performance enhancing additive also increases the aggregate coverage of the binder, resulting in reduced moisture susceptibility of the asphalt composition, such that the resulting composition produces a better pavement composition or waterproofing composition.
[0013] Asphalt compositions as described herein can be used for a variety of purposes. In some embodiments, the asphalt compositions are intended for road construction or other paving purposes, and most of the following description is directed to such paving asphalt compositions. Asphalt compositions intended for road construction or paving purposes are referred to herein as "paving compositions". However, asphalt compositions as described herein can also be used for roofing materials, including asphalt shingles and asphalt roofing membranes. Asphalt compositions can also be used for certain waterproof products, such as waterproof membranes suitable for bridges, parking structures, walking decks, sidewalks, bicycle paths, crawl space barriers, underground structures, etc. Asphalt compositions intended to be used as waterproof materials are referred to herein as "waterproof compositions". The concentrations of asphalt, performance enhancing additives, recycled plastics, aggregates, and other components may vary due to different uses, but it is beneficial for all such asphalt compositions to include recycled plastics with increased storage stability.
[0014] Paving compositions used for paving purposes generally contain two main components: a binder and an aggregate. The binder is generally incorporated with asphalt, and the aggregate has historically been incorporated primarily with minerals such as crushed stone, sand, gravel, dust, slag, and various recycled materials, wherein the recycled materials have historically excluded waste plastics.
[0015] Aggregates
[0016] As used herein, the term "aggregate" includes components that can be distinguished from a binder by detection, such that the binder is used to bond and connect the aggregate. Thus, crushed stone, gravel, slag, rock, dust, sand, various recycled materials, and other components that are not melted into the binder are all classified as being within the meaning of the term "aggregate". Distinguishing by detection includes precision detection, such that dust and fine particles are included in the definition of aggregate. However, detection does mean visual inspection, as well as detection without a lens (such as a microscope). The term "filler" has been used to describe rock dust, lime, and other particulate matter that may be optionally included in the paving composition, and these filler materials are included in the definition of "aggregate" in this specification, such that filler materials are a subset of aggregate. Aggregate composition, shape, size, and quantity are typically selected so that they conform to various hot mix proportioning designs, such as Superpave, Marshall, Hveem, and other designs known in the art.
[0017] Aggregates can include waste plastics. In an exemplary embodiment, based on the gross weight of the aggregates, the aggregates include waste plastics in an amount of about 0 wt % to 100 wt %. In an alternative embodiment, based on the gross weight of the aggregates, the aggregates can include waste plastics in an amount of about 1 wt % to about 100 wt %, or about 5 wt % to about 70 wt %, or about 5 wt % to about 40 wt %. Typically, paving materials include aggregates with various size categories. The particle size distribution or gradient of the aggregates is a feature in the most critical features that determine how paving materials will perform. Aggregates can be used for various gradients, including dense gradients, gap gradients, open gradients, uniform gradients, fine gradients, coarse gradients, etc., or combinations of these gradients. In an exemplary embodiment, large mineral aggregate particles (i.e., larger than about 5 millimeters (mm)) can be replaced by waste plastics to produce an aggregate comprising about 60% by weight of waste plastic particles having a particle size of about 5 mm to about 6 mm, and based on the total weight of the aggregate, can also include about 40% by weight of fine aggregates having a particle size of about 0.15 mm to about 5 mm, and can also include up to about 3% by weight of fillers (such as lime) having an average particle size of about 0.01 mm to about 1 mm. Embodiments including both mineral aggregates and waste plastic aggregates can have mineral aggregates of a first particle size, and the waste plastics can have different particle sizes or the same particle size.
[0018] In another exemplary embodiment, large mineral aggregate particles (i.e., larger than about 10 mm) can be replaced by waste plastics to produce an aggregate containing about 9% by weight of waste plastic particles having a particle size of about 5 mm to about 6 mm, and can also contain about 10% by weight of aggregates having a particle size of about 11 mm. Based on the total weight of the aggregate, the aggregate can also contain about 32% by weight of aggregates having a particle size of about 6.3 mm, about 46% by weight of fine aggregates having a particle size of about 0.15 mm to about 5 mm, and up to about 3% by weight of fillers (such as lime) having an average particle size of about 0.01 mm to about 1 mm.
[0019] In an alternative embodiment, the waste plastic and mineral aggregate are mixed at a temperature above the melting point of the waste plastic. In this embodiment, the molten waste plastic coats the mineral aggregate to form a coated aggregate, wherein the waste plastic substantially surrounds and encloses the mineral aggregate. The waste plastic may not completely enclose the mineral aggregate, such that some portions of the mineral aggregate may be exposed in some embodiments.
[0020] asphalt
[0021] Asphalt is a component of a binder. As used herein, the term "asphalt" is as defined by ASTM, and is a dark brown to black cement-like material, wherein the major component is naturally occurring or asphalt obtained in petroleum processing. Asphalt typically contains saturates, aromatics, resins, and asphaltenes. The terms "asphalt" and "bitumen" are usually used interchangeably, meaning materials in both natural and artificial forms, which are within the scope of the compositions and methods contemplated and described herein.
[0022] The type of asphalt suitable for the composition and method contemplated and described herein is not particularly limited, and includes any naturally occurring, synthetically manufactured and modified asphalt known now or in the future. Naturally occurring asphalt includes natural rock asphalt or asphalt such as Buton asphalt, hard asphalt material, lake asphalt, etc. Synthetic asphalt is often a by-product of oil refining operations, and includes aerated asphalt, blended asphalt, cracked or residual asphalt, petroleum asphalt, propane asphalt, straight run asphalt, hot asphalt, etc. Asphalt-based binders include some types of asphalt (for example, pure asphalt or unmodified asphalt that can be naturally occurring or synthetically manufactured), and can be modified with elastomers, process oils, tackifiers, phosphoric acid, polyphosphoric acid, plastomers, waste tire rubber (GTR), recycled asphalt pavement materials (RAP), recycled asphalt shingles (RAS) and other materials or various combinations of these modifiers.
[0023] Furthermore, it is advantageous to use industrial grade asphalt, including but not limited to paving grade asphalt, for the compositions and methods contemplated and described herein. Non-exclusive examples of paving grade asphalt include, but are not limited to, asphalt having any of the following performance grade ratings ("bitumen" or "asphalt"): PG 46-40, PG 46-34, PG 52-40, PG 52-34, PG 52-28, PG-58-40, PG 58-34, PG 58-28, PG 64-40, PG 64-34, PG 64-28, PG 64-22, PG 64-16, PG 64-10, PG 67-22, PG 70-40, PG 70-34, PG 70-28, PG 70-22, PG 70-16, PG 70-10, PG 76-34, PG 76-28, PG 76-22, PG 76-16, PG 76-10, PG In addition, non-exclusive examples of paving grade asphalt within the scope of the present disclosure include, but are not limited to, paving grade asphalt having any of the following penetration grades: 50 / 70 dmm, 60 / 70 dmm, 60 / 90 dmm, 70 / 100 dmm, 80 / 110 dmm, 120 / 150 dmm, 150 / 180 dmm, 150 / 200 dmm, 160 / 220 dmm, 200 / 300 dmm, and 300+ dmm.
[0024] It is expected that industrial grade asphalt (such as roofing grade asphalt) can be advantageously used for the waterproof composition envisioned and described herein. In such embodiments, the binder composition will be used for roofing applications or other waterproof applications. Suitable roofing grade asphalt includes but is not limited to asphalt with any one of the following hardness grades: 50 / 70 silk meter penetration (dmm pen), 60 / 90 dmm pen, 70 / 100 dmm pen, 80 / 110 dmm pen, 120 / 150 dmm pen, 100 / 150 dmm pen, 150 / 200 dmm pen, 200 / 300 dmm pen and 300+ dmm pen. The hardness grade is determined by the test method described in ASTM D5. In some embodiments of the waterproof composition, based on the gross weight of the waterproof composition, asphalt is present in a concentration of about 40 weight % (wt.%) to about 98 weight % (wt.%). Asphalt can be present in different waterproof binder compositions described herein (that is, binder compositions that can be used for (i) self-adhesive membranes, (ii) shingles or (iii) other waterproof compositions) at different concentrations. For example, in a binder that can be used for a self-adhesive film, the asphalt can be present in a concentration of about 50% to about 60% by weight, or about 51% to about 57% by weight, or about 53% to about 55% by weight. In a binder that can be used for shingles, the asphalt can be present in a concentration of about 20% to about 50% by weight, or about 25% to about 40% by weight, or about 30% to about 35% by weight. Other concentrations can be used for different waterproofing products.
[0025] Recycling plastics
[0026] Recycled plastics may include many types of plastics. For example, recycled plastics may include, but are not limited to, one or more of polystyrene, polyolefins, polyvinyl chloride, polymers made from ethylene propylene diene monomer, ethylene vinyl acetate, polyesters, polytetrafluoroethylene, polyurethanes, polycarbonates, polyamides, polyimides, polyacrylamides, polymethacrylamides, etc. The recycled plastics may be washed before use, such as to remove residues from previous uses of the plastics, and subjected to sorting or other processes. The recycled plastics may be chopped, shredded, crushed, pelletized, or otherwise processed to produce a desired size and shape for further processing.
[0027] Recycled plastics can include plastics that are enumerated with numbers for recycling. The categories of these plastics are listed below, and in an exemplary embodiment, these categories can form some or all of the recycled plastics. However, alternative sources or recycled plastics can also be used.
[0028] Types of plastics .
[0029] There are many different types and varieties of plastics, and many are recyclable. The Society of the Plastics Industry (SPI) has established a classification system as follows:
[0030] Category 1: Polyethylene terephthalate (PET) and polyethylene terephthalate ester (PETE), more commonly known as "polyester". PETE fiber is sold under the trade name (DuPont de Nemours & Co., Wilmington, Del., USA) and PETE film is sold by Wellman, Inc., Fort Mill, SC, USA. PETE film is commonly referred to as (DuPont de Nemours and Company, Wilmington, Del., USA.) Many foods are packaged in PETE, and most clear and colored 2-liter beverage bottles sold in grocery stores are made of PETE, with the exception of opaque substrates which are typically made of high-density polyethylene (HDPE).
[0031] Category 2: High-density polyethylene (HDPE). HDPE is used in plastic milk bottles, water bottles, cosmetic containers, and most plastic grocery and garbage bags.
[0032] Category 3: Polyvinyl chloride (PVC). Most of the PVC produced is used to make plastic pipes and conduits. PVC is also used to produce vinyl siding and vinyl door and window frames. PVC is also used to enclose many items, such as tools and toys, and is still used to produce plastic bottles. PVC can be made flexible by adding phthalates and then used to make raincoats, shower curtains, and rubber boots.
[0033] Category 4: Low-density polyethylene (LDPE). LDPE is used to make lightweight plastic films and for food and sandwich bags.
[0034] Category 5: Polypropylene (PP). Most PP is used to produce car and truck interiors, such as doors and dashboards, although some is used in food packaging. Another important use is in fibers for clothing and carpets.
[0035] Category 6: Polystyrene (PS). Polystyrene is used to produce polystyrene foam, which is used for packaging, insulation, and food packaging. PS is also used in transparent, thin, and rigid food containers, such as those for salads and baked goods. Many household items, including broom handles, TV cases, computer cases, and dry cosmetic containers, are produced from PS.
[0036] Class 7 covers any plastic that does not fall into any of Classes 1 to 6. These include polytetrafluoroethylene (PTFE), polyurethane (PU), polycarbonate (PC), polyamides (PA) such as nylon, and polyacrylamide and polymethacrylamide (PMA) used as absorbents in diapers and potting soil.
[0037] Waste Plastics
[0038] The waste plastics used as aggregates in the paving composition may include unclassified plastics or classified plastics. The paving composition can provide sufficient performance and durability with a variety of different types of plastics, and different types of plastics can be mixed or combined in almost any way. For example, the waste plastic aggregates in one part of the paving composition may mainly include one type of plastic, and the waste plastic aggregates in another part of the same paving composition may mainly include different types of plastics or different mixtures of various types of plastics. In this way, unclassified waste plastics can be used for aggregates in the paving composition, and therefore the cost of classification can be avoided. However, classified waste plastics can be used in alternative embodiments.
[0039] The waste plastics used as aggregates can be formed into desired sizes, and aggregates can be formed into desired sizes using a variety of techniques. If the waste plastics are too large, then their size can be reduced by chopping, shredding, grinding or other techniques. If the waste plastics are too small, then granulation or agglomeration can be performed by melting, partial melting or compacting. For example, the waste plastics used as aggregates can be formed into materials with an average particle size of about 20 mm to about 25 mm, but other average particle sizes are also possible. In alternative embodiments, the average particle size of the waste plastics can be about 20 mm, or about 10 mm, or about 6 mm to 7 mm or other sizes. In some embodiments, the waste plastics can have a wide range of particle sizes, and some of these particles are larger than other particles.
[0040] Replacing mineral aggregates with waste plastics has the additional advantage of reducing the gross weight of the asphalt composition. For example, based on the gross volume of the paving composition, a standard paving composition comprises about 88% by weight of mineral aggregates and about 12% by weight of asphalt. Based on the gross volume of the paving composition, a hypothetical paving composition comprising about 12% by volume of asphalt and about 88% by volume of waste plastic aggregates will be about 62% lighter than a standard paving composition of the same volume comprising about 88% by volume of mineral aggregates. In an exemplary embodiment of the paving composition, coarse mineral aggregates (20mm, 10mm and 6.3mm) are replaced by waste plastic aggregates (5mm to 6mm) on a volume basis, and the paving composition containing waste plastic aggregates is about 32% lighter than the standard paving composition containing coarse mineral aggregates. In a hypothetical example, replacing mineral aggregate granules of building roof shingles with waste plastic aggregate granules on a volume basis will be able to reduce the weight of building roof shingles by about 22%. The reduction in the weight of the paving composition can help solve transportation problems, as well as provide other benefits. The reduction in shingle weight reduces the loads on the roof structure, and similar advantages can be applied to other waterproofing structures.
[0041] Recycled plastics
[0042] Recycled plastics are melted and mixed in the binder together with asphalt. The particle size of recycled plastics can vary widely, because particles will melt to be mixed in the binder. As measured by ASTM D7173, recycled plastics tend to reduce the storage stability of binders, and tests have shown that some types of recycled plastics have reduced the stability of binders more than other types. For example, based on the gross weight of the binder, recycled low-density polyethylene can be mixed in the binder to form a stable product with a concentration of at most about 4 % by weight of the binder. However, polypropylene or other types of plastics may need even lower concentrations to form a stable binder, or may not form a stable binder at any concentration. Therefore, the recycled plastics for melting and mixing in the binder can be classified so that in one embodiment, based on the gross weight of recycled plastics, recycled plastics are polyethylene more than about 50 % by weight. In alternative embodiments, the recycled plastic incorporated into the binder may be 70 wt% polyethylene, or 80 wt% polyethylene, or 90 wt% polyethylene, or 95 wt% polyethylene, or 98 wt% polyethylene, or even 100 wt% polyethylene, based on the total weight of the recycled plastic. Gel permeation chromatography can effectively distinguish recycled plastic from performance enhancing additives.
[0043] Performance Enhancing Additives
[0044] The performance enhancing additive is incorporated into the binder together with the recycled plastic. The performance enhancing additive is selected from a low molecular weight polyolefin, a glycidyl compound, or a combination thereof. The low molecular weight polyolefin has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, and may be referred to as a low molecular weight (LMW) polyolefin. As used herein, the term "low molecular weight polyolefin" means an olefin-containing polymer, or a blend of two or more olefin-containing polymers, each of which has a weight average molecular weight (MW) of about 500 Daltons to about 30,000 Daltons. w ) and comprises one or more olefinic monomers, wherein the olefinic monomers are selected from: ethylene, propylene, butene, hexene and octene. Therefore, LMW polyolefins can be homopolymers comprising only a single type of olefin monomer, or copolymers comprising two or more types of olefin monomers. In addition, as used herein, the term LMW polyolefin includes but is not limited to polyolefin waxes, i.e., polyolefins that are solid at or near room temperature and have low viscosity when above their melting point. Some Fischer-Tropsch waxes (i.e., Fischer-Tropsch waxes that meet the characteristics of low molecular weight polyolefins defined above but are made of carbon monoxide and hydrogen) can also be used in the asphalt compositions contemplated and described herein.
[0045] Thermally degradable waxes are also exemplary of LMW polyolefins, wherein, as described above, the thermally degradable waxes have a weight average molecular weight of from about 500 Daltons to about 30,000 Daltons. In various embodiments, the thermally degradable waxes may be formed from natural polymers or recycled polymers.
[0046] In some embodiments, low molecular weight polyolefin can be functionalized, wherein low molecular weight polyolefin can be functionalized homopolymer or copolymer.In an exemplary embodiment, functionalized low molecular weight polyolefin comprises one or more functional groups, includes but not limited to acid, ester, amine, amide, ether and anhydride (such as maleic anhydride).In addition, low molecular weight polyolefin can be oxidized.
[0047] In an exemplary embodiment, the LMW polyolefin is an oxidized high density polyethylene. High density polyethylene has a density of about 0.93 grams per cubic centimeter (g / cc) to about 0.97g / cc or higher, and the oxidized high density polyethylene has a density equal to or greater than that of high density polyethylene, depending on the degree of oxidation. Exemplary oxidized high density polyethylene has a density of at least 0.93g / cc, 0.94g / cc, 0.95g / cc, 0.96g / cc, 0.97g / cc, 0.98g / cc, 0.99g / cc or 1.00g / cc. In contrast, low density polyethylene has a density of about 0.91g / cc to about 0.93g / cc. Low density polyethylene tends to include multiple side chains in the polymer chain, while high density polyethylene has minimal polymer branching. Oxidized polyethylene is the reaction product of polyethylene and oxygen, and can be prepared by different techniques. Oxidized polyolefins will have an acid value, which is defined as the amount of potassium hydroxide in milligrams required to neutralize 1 gram of polyolefin under fixed conditions. For example, one set of fixed conditions is ASTM 1386-83.
[0048] In an exemplary embodiment, based on the gross weight of low molecular weight polyolefin, low molecular weight polyolefin has an olefin content of about 50 wt % to about 100 wt %.Based on the gross weight of low molecular weight polyolefin, exemplary low molecular weight polyolefin has at least about 55 wt %, 60 wt %, 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt % or 95 wt %, and is no more than about 100 wt %, 98 wt %, 95 wt %, 92 wt %, 90 wt %, 85 wt %, 80 wt % or 75 wt % olefin content (in wt % as unit) independently.
[0049] As already mentioned, in one exemplary embodiment, the low molecular weight polyolefin has a weight average molecular weight (MW) of about 500 Daltons to about 30,000 Daltons. w In various embodiments, the low molecular weight polyolefin has an M in Daltons of at least about 500, 1,000, 2,000, 3,000, 4,000, 5,000, 6,000, or 7,000, and independently no more than about 30,000, 20,000, 15,000, 12,000, or 10,000. w In the case where the low molecular weight polyolefin comprises a combination of more than one type of polyolefin, the M of each type of polyolefin in the combination is wEach can be within the range of about 500 Daltons to about 30,000 as described above. The weight average molecular weight of the low molecular weight polyolefin disclosed herein can be determined by gel permeation chromatography (GPC), a technique known in the art. For the purpose of GPC, the sample to be measured can be dissolved in 1,2,4-trichlorobenzene at about 140°C and a concentration of about 2.0 mg / ml. The solution (200 microliters (μL)) is injected into the GPC at a flow rate of about 1.0 mL / min, and the GPC comprises two PLgel 5 microns (μm) mixed D (300x7.5mm) columns maintained at about 140°C. The instrument can be equipped with two detectors, such as a refractive index detector and a viscosity detector. The molecular weight (weight average molecular weight, Mw) is determined using a calibration curve generated by a set of linear polyethylene narrow weight average molecular weight standards.
[0050] Generally speaking, suitable low molecular weight polyolefins include, but are not limited to, polyethylene homopolymers; polypropylene homopolymers; copolymers of two or more of ethylene, propylene, butene, hexene and octene; functionalized derivatives of the above homopolymers; functionalized derivatives of the above copolymers; or combinations of unfunctionalized and functionalized low molecular weight polyolefins. Some Fischer-Tropsch waxes (i.e., Fischer-Tropsch waxes that meet the characteristics of low molecular weight polyolefins defined above but are made from carbon monoxide and hydrogen) may also be used in the asphalt compositions contemplated and described herein. Examples of suitable functionalized low molecular weight polyolefins include, but are not limited to, maleated polyethylene, maleated polypropylene, ethylene acrylic acid copolymers, ethylene vinyl acetate copolymers, oxidized polypropylene, oxidized polyethylene (including oxidized low molecular weight polyethylene), and combinations thereof.
[0051] In an exemplary embodiment, the low molecular weight polyolefin is selected from the group consisting of polyethylene, oxidized polyethylene having an acid value of about 5 milligrams to about 40 milligrams of potassium hydroxide per gram (mg KOH / gm), polypropylene, maleated polypropylene, and combinations thereof. In alternative embodiments, the low molecular weight polyolefin is polyethylene, or oxidized polyethylene, or polypropylene, or maleated polypropylene, a copolymer of ethylene and propylene, or a combination thereof.
[0052] Glycidyl compounds include ethylene (meth) glycidyl acrylate polymers. As used herein, the term "(meth) acrylate" means an acrylate compound that may or may not include a methyl group, so the term includes "... acrylate" and "... methacrylate". Ethylene (meth) glycidyl acrylate polymers may include about 4% to about 20% by weight of glycidyl (meth) acrylate and about 80% to about 96% by weight of ethylene in the polymer. However, in an alternative embodiment, ethylene (meth) glycidyl acrylate polymers include about 2% to about 30% by weight of glycidyl (meth) acrylate and about 70% to about 98% by weight of ethylene. Ethylene (meth) glycidyl acrylate polymers have a weight average molecular weight of about 500 Daltons to about 30,000 Daltons. Binder compositions comprising glycidyl compounds typically also include polyphosphoric acid as a component.
[0053] The glycidyl compound may include an ethylene (meth) glycidyl acrylate copolymer, a terpolymer, a polymer having more than three monomers, or a mixture of the above compounds. In an exemplary embodiment, the acrylate compound includes a polymer having more than one monomer, and the acrylate compound may be free of homopolymers, wherein "free of" homopolymers means that the glycidyl compound may contain less than about 1% by weight of homopolymers based on the total weight of the glycidyl compound. Additional monomers in the polymer may include (meth) acrylates, butyl (meth) acrylates, and similar compounds, including combinations thereof. A variety of polymers based on glycidyl (meth) acrylates can effectively improve the storage stability of the adhesive. Therefore, the ethylene (meth) glycidyl acrylate polymer can be formed by two or more monomers selected from the group of ethylene, glycidyl acrylate, glycidyl methacrylate, methyl acrylate, methyl methacrylate, butyl acrylate, and butyl methacrylate. The low molecular weight of about 500 Daltons to about 30,000 Daltons is expected to provide improved storage stability compared to other glycidyl compositions containing ethylene glycidyl (meth)acrylate polymers having a molecular weight greater than 30,000 Daltons.
[0054] In various exemplary embodiments, the performance enhancing additive includes: a glycidyl compound without polyolefin; a polyolefin without a glycidyl compound; and a combination of a glycidyl compound and a polyolefin. In an exemplary embodiment, the combination of a glycidyl compound and a polyolefin more specifically includes: a combination of oxidized low molecular weight high density polyethylene, a glycidyl compound and polyphosphoric acid; a combination of low molecular weight polypropylene, a glycidyl compound and polyphosphoric acid; and maleated polypropylene, a glycidyl compound and polyphosphoric acid. Other specific combinations of polyolefins and glycidyl compounds are also possible.
[0055] additive
[0056] In some embodiments, the asphalt compositions described herein may also include other additives. The use of additional additives such as plastomers, elastomers, or both for asphalt compositions (including binders) is well known in the industry, and these additives can expand the temperature range over which the asphalt compositions can be used without causing serious defects or failures. Plastomers and elastomers are typically polymers of one or another type and can be used in asphalt compositions, such as binders for paving compositions, or in waterproof compositions, or for other purposes. In addition to performance enhancing additives, the asphalt compositions contemplated herein may optionally include one or more polymers, which are present in a total amount of about 0.5% by weight to about 30% by weight, based on the gross weight of the asphalt composition. Non-limiting examples of polymers suitable for modifying the asphalt compositions contemplated herein include natural or synthetic rubbers, including scrap tire rubber (GTR), devulcanized GTR, micronized GTR, butyl rubber, styrene / butadiene rubber (SBR), styrene / ethylene / butadiene / styrene terpolymers (SEBS), polybutadiene, polyisoprene, ethylene / propylene / diene (EPDM) terpolymers, and styrene / conjugated diene block or random copolymers, such as styrene / butadiene (including styrene / butadiene / styrene copolymers (SBS)), styrene / isoprene, styrene / isoprene / styrene (SIS), and styrene / isoprene-butadiene block copolymers. Block copolymers may be branched or linear, and may be diblock, triblock, tetrablock, or multiblock. In addition to asphalt, performance enhancing additives, and recycled plastics, the binder may optionally include the polymers listed above as well as other polymers for improving performance.
[0057] In some embodiments, the asphalt compositions contemplated herein may include additional additives. The asphalt compositions include a binder for the paving composition and a waterproofing composition, and also include other embodiments not specifically described. Non-exclusive examples of such additives suitable for inclusion in the asphalt compositions contemplated and described herein include, but are not limited to, plastomers, waxes (wherein the wax may also be a polymer), polyphosphoric acid, flux oils, plasticizers, antioxidants, tackifiers, processing aids, UV protection additives, and the like. Exemplary non-exclusive waxes include ethylene bis stearamide wax (EBS), Fischer-Tropsch wax (FT) (outside the definition of "polyolefin" provided herein), oxidized Fischer-Tropsch wax (FTO) (outside the definition of "polyolefin" provided herein), alcohol waxes, silicone waxes, petroleum waxes (such as microcrystalline waxes or paraffin waxes), natural waxes, and other synthetic waxes. Exemplary plasticizers include hydrocarbon oils (e.g., paraffin oils, aromatic oils, and naphthenic oils), long chain alkyl diesters (e.g., phthalates (such as dioctyl phthalate) and adipates (such as dioctyl adipate)), sebacates, glycols, fatty acids, phosphates and stearates, epoxy plasticizers (e.g., epoxidized soybean oil), polyether and polyester plasticizers (which can also be polymers), alkyl monoesters (e.g., butyl oleate), long chain partial ether esters (e.g., butyl oleate cellosolve), etc. Exemplary tackifiers include rosin and its derivatives; terpenes and modified terpenes; aliphatic, alicyclic, and aromatic resins (C5 aliphatic resins, C9 aromatic resins, and C5 / C9 aliphatic / aromatic resins); hydrogenated hydrocarbon resins; terpene-phenol resins; and combinations thereof. Exemplary oils include flux oils (eg, paraffinic, aromatic, and naphthenic), bio-oils, corn oil, soybean oil, tall oil, reclaimed oils, recycled engine oils, residual recycled engine oil (REOB), and combinations thereof.
[0058] In an exemplary embodiment, the asphalt composition including the paving composition, the waterproofing composition and other compositions is free of cement, where "free of cement" means that the cement is contained in an amount of less than about 0.1% by weight based on the total weight of the asphalt composition. This means that the binder is also free of cement, so that the binder contains cement in an amount of less than about 0.1% by weight. As used herein, cement includes, but is not limited to, ordinary Portland cement, high early strength Portland cement, ultra-high early strength cement, medium heat Portland cement, white Portland cement, blast furnace cement, silicate cement, high alumina cement, expansive cement, blast furnace colloidal cement, colloidal cement, ultra-fast hardening cement, white cement, fly ash cement, sulfate-resistant cement, shotcrete cement, and combinations thereof.
[0059] Binder
[0060] As described above, the binder comprises asphalt, a performance enhancing additive and recycled plastic. In an exemplary embodiment, the binder comprises a performance enhancing additive in an amount of about 0.1% by weight to about 5% by weight; and as described above, the amount of recycled plastic is about 1% by weight to about 20% by weight based on the total weight of the binder. For example, the binder may comprise about 0.1% by weight to about 5% by weight of a low molecular weight polyolefin; and / or about 0.1% by weight to about 5% by weight of a glycidyl compound and about 0.1% by weight to about 1% by weight of polyphosphoric acid, all based on the total weight of the binder. In an alternative embodiment, based on the total weight of the binder, the binder may comprise about 0.5% by weight to about 5% by weight of a low molecular weight polyolefin, or about 0.5% by weight to about 3% by weight of a low molecular weight polyolefin. In various embodiments, the binder may be free of low molecular weight polyolefins or glycidyl compounds, but the binder does not contain both low molecular weight polyolefins and glycidyl compounds at the same time when used.
[0061] In an exemplary embodiment, the low molecular weight polyolefin and / or the glycidyl compound can be combined with the aggregate, so the binder can be free of both the low molecular weight polyolefin and the glycidyl compound before mixing with the aggregate. However, at least some of the low molecular weight polyolefin and / or the glycidyl compound are then melted into the aggregate in the final paving composition. It is possible that some of the low molecular weight polyolefin and / or the glycidyl compound may not be melted into the binder, and therefore remain with the aggregate, so the amount of the low molecular weight polyolefin and / or the glycidyl compound can be increased to ensure that it is sufficiently melted into the binder to obtain the desired performance. As described above, in some embodiments, the low molecular weight polyolefin can be functionalized. The binder can also optionally include additives other than performance enhancing additives and recycled plastics. Based on the gross weight of the binder, other optional additives can be included in an amount of about 0 weight % to about 30 weight %. Based on the gross weight of the binder, the binder includes asphalt in an amount of about 25 weight % to about 99.9 weight %. Recycled plastics may also be added to the aggregate as recycled plastics to form part of the reinforcing aggregate. Some of the recycled plastics may then be melted into the binder, wherein the recycled plastics melted into the binder are referred to herein as "recycled plastics," as described above. Any of the recycled plastics not melted into the binder is retained with the aggregate as waste plastics and forms part of the aggregate in the final paving composition. As described above, "waste plastics" is a term used for recycled plastics that are not melted into the binder and used as aggregate in the paving composition.
[0062] Binders that contain recycled plastics but do not contain performance enhancing additives tend to be unstable unless the binder contains recycled plastics at very low concentrations based on the total weight of the binder. For the low-density polyethylene recycled plastics used in this work, 4% by weight of low-density polyethylene forms a stable binder based on the total weight of the binder. If the recycled plastics include polypropylene or other types of plastics except low-density polyethylene, the binder tends to become unstable at even lower concentrations of recycled plastics, or may be unstable at all concentrations. Performance enhancing additives increase the amount of recycled plastics that can be incorporated into a stable binder composition. Therefore, in an exemplary embodiment, based on the total weight of the binder, the binder can include a low-density polyethylene in an amount greater than 4% by weight, and wherein the binder also includes a performance enhancing additive. For example, the binder can include about 4% by weight to about 20% by weight of low-density polyethylene, wherein the polyethylene is recycled plastic. In another embodiment, the binder includes about 4% by weight to about 8% by weight of low-density polyethylene from recycled plastics.
[0063] Paving composition
[0064] The paving composition is intended for use in pavements, parking lots, driveways and other similar structures. The paving composition is suitable for sustaining motor vehicle traffic. The paving composition comprises a binder and an aggregate as described above. The binder is present in the paving composition in an amount of about 1 wt % to about 15 wt %, and the aggregate is present in an amount of about 85 wt % to about 99 wt %, based on the total weight of the paving composition.
[0065] The binder is stable, wherein a stable binder means that the top portion and the bottom portion of the binder have approximately the same softening point. In this specification, a "stable binder" is defined by a top sample and a bottom sample having a softening point difference (absolute value) of less than 5°C. If the top sample softening point and the bottom sample softening point of the binder are within 5°C of the other, the binder is considered to be stable, regardless of which of the top sample and the bottom sample has a higher softening point. The top sample and the bottom sample of the binder are obtained using a separation test as described in ASTM D7173. The softening points of the top sample and the bottom sample are then determined using a ring and ball softening point test, wherein the ring and ball softening point test is described by ASTM D36. The ASTM D7173 separation test or "Standard Practice for Determining the Separation Tendency of Polymer from Polymer Modified Asphalt" provides consistent sampling of the top and bottom portions of an asphalt composition (such as a binder). The Ring and Ball Softening Point Test or ASTM D36 is a consistent method for measuring the softening point of asphalt compositions such as binders. Other countries sometimes use other parameters such as the complex modulus G* to determine storage stability. For example, for the Qatar national specification, the specification is ΔG*<20%. However, for this specification, the definition provided above is used. A stable binder is important for preparing a paving composition that provides consistent quality for the construction of roads, parking lots and other structures intended to carry motor vehicles.
[0066] Another important parameter of the binder is its workability, processability or pumpability, which is determined by the viscosity of the binder at or near about 135° C. according to ASTM D4402. It is widely accepted in the world paving industry that the viscosity of the binder at or near about 135° C. should be less than about 3,000 centipoise (cPs) in order for it to have acceptable workability, processability or pumpability. Viscosities above about 3,000 cPs produce a binder with poor workability, processability and / or pumpability.
[0067] In an alternative embodiment, the paving composition comprises aggregates, wherein the aggregates comprise waste plastics in an amount of up to 100% by weight based on the total weight of the aggregates. For example, the aggregates in the paving composition may comprise from about 1% by weight to 100% by weight of waste plastics. The paving composition also includes a binder, wherein the binder comprises a low molecular weight polyolefin of asphalt and a performance enhancing additive, but the binder may be free of recycled plastics. The binder may also be free of glycidyl compounds. The binder may also contain other additives as described above. It has been found that the binder in combination with the low molecular weight polyolefin provides better coverage of both waste plastic aggregates and mineral aggregates, and produces a denser paving composition, compared to the same binder without the low molecular weight polyolefin as described for the performance enhancing additive.
[0068] Waterproof composition
[0069] Many different waterproof compositions incorporating recycled plastics are possible. This includes roofing membranes, shingles, and other waterproof structures. The waterproof composition comprises a waterproof binder, and sometimes comprises a substrate, a surface layer, a backing layer, and other optional components. The substrate may be a polyester mat, a glass fiber mat, a glass fiber reinforced polyester mat, or other materials. The surface layer may be a mineral granular material, i.e., a granular material made of one or more of recycled plastics, sand, talc, coatings, plastic films, metal films, etc. The backing layer may be sand, talc, plastic films, metal films, etc. The waterproof composition comprises a waterproof binder, wherein the waterproof binder comprises asphalt, recycled plastics, performance enhancing additives, optionally fillers, and optionally other compounds. Based on the gross weight of the waterproof binder, the waterproof binder comprises recycled plastics in an amount of about 1 wt % to about 20 wt %, performance enhancing additives in an amount of about 1 wt % to about 10 wt %, and fillers in an amount of 0 wt % to 70 wt %. In addition to the recycled plastics and performance enhancing additives, the waterproof binder may also comprise additional additives in an amount of about 0 wt % to about 40 wt %, based on the gross weight of the waterproof binder. The waterproof composition may also comprise other components. For example, the shingles include at least one binder. In various embodiments, the filler may be limestone, rock dust, fly ash, other materials, or combinations thereof.
[0070] Method for preparing paving composition
[0071] The paving composition is prepared by mixing the components of the binder to prepare the binder, and mixing the binder with the aggregate to prepare the paving composition. In particular, the binder can be prepared by mixing the above-mentioned asphalt, the above-mentioned performance enhancing additive and the above-mentioned recycled plastic in a molten state to prepare the binder. In various embodiments, other additives (in addition to the performance enhancing additive and the recycled plastic) can be optionally mixed with the binder and / or the aggregate. The binder can be mixed at a temperature of about 90°C to about 220°C, or in another embodiment, the binder can be mixed at a temperature of about 100°C to about 190°C. In a "wet" process, the performance enhancing additive and the recycled plastic are melted into the binder. The binder can then be mixed with the aggregate to prepare the paving composition.
[0072] In the "dry" method, performance enhancing additives and / or waste plastics can be mixed with aggregates to form enhanced aggregates, which can then be mixed with a binder to form a paving composition. However, in alternative embodiments, waste plastics and / or performance enhancing additives can be mixed with a binder before mixing the binder and aggregates. In this case, recycled plastics are mixed into the paving composition together with the aggregates, the binder or separately, and some of the waste plastics are melted into the binder and are referred to herein as "recycled plastics", as described above. Some of the recycled plastics remain separate and distinguishable from the binder and are used as aggregates, and are referred to herein as "waste plastics", also mentioned above. The performance enhancing additives can be mixed with the binder before being mixed into the aggregates, but in other embodiments, the performance enhancing additives can be included in the enhanced aggregates and then mixed with the binder when the binder and aggregates are combined. Therefore, some of the performance enhancing additives can be incorporated into the binder, but some of the performance enhancing additives can remain different from the binder and are still used to stabilize and improve the performance of the paving composition containing waste plastics as a component of the aggregate. Depending on the type of equipment used, it may be easier for some producers to mix recycled plastics and / or performance enhancing additives with the aggregate prior to combining with the binder.
[0073] Aggregates as described above are mixed with a binder to prepare a paving composition. In embodiments where the aggregates contain waste plastics, the aggregates may be mixed with a binder in a manner that prevents or minimizes melting of the waste plastics of the aggregates. This can be achieved by mixing the aggregates and the binder at a temperature below the melting point of the waste plastics, or by quickly mixing the aggregates and the binder and then cooling the paving composition so that the waste plastics are not exposed to a temperature above the melting point of the waste plastics for a long time. In addition, some of the waste plastics may melt during or after the mixing of the aggregates and the binder, because the binder may be able to incorporate some additional plastic material from the waste plastics. Alternatively, some of the molten waste plastics may remain separated from the binder in the mixture around the edges of the solid waste plastic particles, and then the molten waste plastics may be resolidified into solid aggregates, which can be distinguished from the binder by detection when the paving composition is cooled. In an exemplary embodiment, the binder and the waste plastics are mixed at a temperature of about 90°C to about 220°C, but in an alternative embodiment, the binder and the aggregates are mixed at a temperature of about 100°C to about 190°C.
[0074] In an alternative embodiment, the method includes mixing waste plastic with mineral aggregate at a temperature exceeding the melting point of waste plastic. Mix waste plastic and mineral aggregate under conditions that can effectively coat mineral aggregate with waste plastic, so that waste plastic substantially encloses mineral aggregate to form enclosed aggregate. The enclosed aggregate can then be mixed with a binder to form a paving composition. In some embodiments, mineral aggregate can be completely enclosed in waste plastic, but in an alternative embodiment, minerals can be partially enclosed. In an exemplary embodiment, about 20% to 100% of the surface area of mineral aggregate can be enclosed in waste plastic. However, in an alternative embodiment, about 50% to 100% or about 75% to 100% of the surface area of mineral aggregate is enclosed by waste plastic.
[0075] Example
[0076] Several experiments were performed as described below.
[0077] Table 1 provides 21 binders prepared and tested as described below. These tests show that storage stability is increased when the performance enhancing additive comprises (1) a low molecular weight oxidized polyethylene homopolymer, (2) a glycidyl compound, (3) a low molecular weight polyethylene homopolymer, (4) a glycidyl compound in combination with polyphosphoric acid and a Fischer-Tropsch wax, and / or (5) a thermally degraded wax. Table 1 provides examples of a "wet" process in which recycled plastic is melted into the binder. The recycled plastic in the examples described in Table 1 is low density polyethylene. Storage stability is clearly demonstrated as the absolute value (ABS) of the drop point difference (°C top - °C bottom), where a difference greater than 5°C is considered unstable. When a high molecular weight glycidyl compound #2 was used, Run #14 showed acceptable storage stability, but the viscosity of 9360 cps at 135°C was much higher than the 3000 cps maximum. Run #20 shows that when the low-density polyethylene recycled plastic concentration reaches 8 wt%, the glycidyl compound and polyphosphoric acid do not produce a stable product, but Run #5, Run #6 and Run #7 show that at a low-density polyethylene recycled plastic concentration of 7 wt%, the glycidyl compound and polyphosphoric acid can effectively prepare a stable product.
[0078] Blend #1, Blend #2, Blend #4, and Blend #8 prepared in Table 1 followed the following blending process: recycled plastic was added to molten asphalt at 180°C and mixed in a high shear mixer at about 3500 rpm for 4 hours. Blend #9, Blend #16, Blend #17, and Blend #21 were stabilized by adding recycled plastic and LMW polyethylene homopolymer to molten asphalt at 180°C and mixing in a high shear mixer at about 3500 rpm for 4 hours by following the above blending process. Blend #12 was stabilized by adding recycled plastic and Fischer-Tropsch wax to molten asphalt at 180°C and mixing in a high shear mixer at about 3500 rpm for 4 hours by following the above blending process. Blend #3, Blend #5, Blend #6 and Blend #10 were prepared by following the above blending process: Recycled plastic, LMW oxidized polyethylene homopolymer and glycidyl compound were added to molten asphalt at 180°C and mixed in a high shear mixer at about 3500 rpm for 2 hours, after the 2 hours of mixing were completed, PPA (polyphosphoric acid) was then added and mixed for another 2 hours. Blend #11 was prepared by following the above blending process: Recycled plastic, Fischer-Tropsch wax and glycidyl compound were added to molten asphalt at 180°C and mixed in a high shear mixer at about 3500 rpm for 2 hours, after the 2 hours of mixing were completed, PPA (polyphosphoric acid) was then added and mixed for another 2 hours. Blend #7, Blend #13, Blend #14, Blend #15 and Blend #20 were prepared by following the above blending process and by the following steps: Recycled plastic and glycidyl compound (high molecular weight or low molecular weight) were added to molten asphalt at 180°C and mixed in a high shear mixer at about 3500 rpm for 2 hours, after the 2 hours of mixing was completed, PPA (polyphosphoric acid) was then added and mixed for another 2 hours. Blend #18 and Blend #19 were stabilized by following the above blending process by adding recycled plastic and thermally degraded wax to molten asphalt at 180°C and mixing in a high shear mixer at about 3500 rpm for 4 hours.
[0079] Table 1, Part 1
[0080]
[0081]
[0082]
[0083] Table 1, part 2
[0084]
[0085]
[0086]
[0087] Table 1, Part 3
[0088]
[0089]
[0090]
[0091] Compositions are provided in weight %, based on the total weight of the binder composition. Using the above conditions, the low molecular weight high density oxidized polyethylene homopolymer has a weight average molecular weight of 8,000 to 9,000 Daltons.
[0092] LMW Oxidized PE Homopolymer #1: Honeywell 7686.
[0093] LMW Oxidized PE Homopolymer #2: Produced by Westlake Chemical EE-2.
[0094] LMW PE Homopolymer #1: Honeywell 7205.
[0095] LMW PE Homopolymer #2: Honeywell 7467.
[0096] LMW PE Homopolymer #3: Honeywell 7287.
[0097] High molecular weight glycidyl composition #1 is 4170.
[0098] High molecular weight glycidyl composition #2 is AX-8900.
[0099] Thermally Degraded Wax #1: AW115.91 produced by GreenMantra Technologies.
[0100] Thermally degraded wax #2: 104N produced by Lion Chemtech Co., Ltd.
[0101] Brookfield Viscosity: ASTM D4402, Standard Test Method for Viscosity of Bitumen at Elevated Temperatures Using a Rotational Viscometer.
[0102] G* (complex modulus), Δ (phase angle): According to ADTM D7175, Standard Test Method for Rheological Properties of Asphalt Binders Using Dynamic Shear Rheometer; G* / sin(Δ) can be calculated from G* and Δ. Values greater than or equal to 1.00 kilopascals (kPa) are considered passing values at both 70°C and 76°C.
[0103] RTFO (Rolling Thin Film Oven) Test: ASTM D2872, Standard Test Method for Effects of Heat and Air on Moving Films of Asphalt (Rolling Thin Film Oven Test). Values greater than or equal to 2.20 kPa are considered passing values at both 70°C and 76°C.
[0104] MSCR (Multiple Stress Creep and Recovery) Test: ASTM D7405, Standard Test Method for Multiple Stress Creep and Recovery (MSCR) of Asphalt Binders Using a Dynamic Shear Rheometer.
[0105] R3.2: Average recovery rate at 3.2 kPa.
[0106] Jnr3.2: Irreversible creep compliance at 3.2 kPa. Values less than or equal to 4.50 kPa are considered pass values at both 70°C and 76°C.
[0107] Jnr diff: The difference between the irrecoverable creep compliance of 0.100 kPa and 3.200 kPa.
[0108] Multiple Stress Creep Recovery (MSCR) testing, using the method described in AASHTO T350-14 and the specifications in AASHTO M332-14.
[0109] Separation Test: ASTM D7173, Standard Practice for Determining the Tendency of a Polymer to Separate from a Polymer-Modified Bitumen. Softening Point Test: ASTM D36, Standard Test Method for Softening Point of Bitumen (Ring-Ball Apparatus).
[0110] ABS (Difference (top - bottom)), ° C. Values less than or equal to 5 ° C. were considered to pass.
[0111] PG: Performance Grade, AASHTO M320, Standard Specification for Performance-Graded Asphalt Binders.
[0112] Note: A. The rows titled (Low molecular weight polyethylene homopolymer #2; Low molecular weight polyethylene homopolymer #3; Thermally degraded wax #1; and Thermally degraded wax #2) present in Table 1, Part 3 have values of zero (0) in both Part 1 and Part 2 of Table 1.
[0113] The melt flow index (MFI) of 4170 is 8. The MFI of AX8900 is 6. AX8840 has an MFI of 5 and a molecular weight of 105,000. MFI is often used to approximate molecular weight. AX8840 is similar to 4170 and AX 8900 is a copolymer of ethylene and glycidyl methacrylate. Therefore, based on the MFI value, it is clear that 4170 (High molecular weight glycidyl composition #1) and AX 8900 (High Molecular Weight Glycidyl Composition #2) has a molecular weight greater than the glycidyl methacrylate copolymer used in the above examples. The molecular weight of 4710 is 68,205 Daltons, and the reported The molecular weight of AX8840 is 71,190 Daltons.
[0114] The above examples show that the binder can include recycled plastic in an amount of about 4 wt % to about 8 wt % based on the total weight of the binder. However, the upper limit is not clearly defined. The use of the performance enhancing additive enables the incorporation of recycled plastic in an amount greater than 4 wt %, where in the absence of the performance enhancing additive, an unstable binder is found at 4 wt % or more of recycled plastic.
[0115] Table 2 shows five paving compositions comprising asphalt and high density polyethylene (HDPE), where the HDPE is a recycled plastic melted into a binder. The results show that when the HDPE concentration is 4 wt% or greater (based on the total weight of the binder), the HDPE and asphalt are inherently unstable as shown by the ABS difference (top to bottom), where HDPE concentrations above 4 wt% have a top to bottom softening point difference of greater than 5°C. These tests show that storage stability is increased when the performance enhancing additive comprises (1) a low molecular weight oxidized polyethylene homopolymer, (2) a glycidyl compound, and (3) polyphosphoric acid.
[0116] Table 2 .
[0117]
[0118] Compositions are provided in weight %, based on the total weight of the binder composition.Brookfield Viscosity: ASTM D4402, Standard Test Method for Viscosity of Asphalt at Elevated Temperatures Using a Rotational Viscometer.
[0119] G* (complex modulus), Δ (phase angle): According to ADTM D7175, Standard Test Method for Rheological Properties of Asphalt Binders Using Dynamic Shear Rheometer; G* / sin(Δ) can be calculated from G* and Δ. Values greater than or equal to 1.00 kilopascals (kPa) are considered passing values.
[0120] RTFO (Rolling Thin Film Oven) Test: ASTM D2872, Standard Test Method for Effects of Heat and Air on Moving Films of Asphalt (Rolling Thin Film Oven Test). Values greater than or equal to 2.20 kPa are considered a passing value.
[0121] MSCR (Multiple Stress Creep and Recovery) Test: ASTM D7405, Standard Test Method for Multiple Stress Creep and Recovery (MSCR) of Asphalt Binders Using a Dynamic Shear Rheometer.
[0122] R3.2: Average recovery rate at 3.2 kPa.
[0123] Jnr3.2: Irreversible creep compliance at 3.2 kPa. Values less than or equal to 4.50 kPa are considered pass values at both 70°C and 76°C.
[0124] Jnr diff: The difference between the irrecoverable creep compliance of 0.100 kPa and 3.200 kPa.
[0125] Multiple Stress Creep Recovery (MSCR) testing, using the method described in AASHTO T350-14 and the specifications in AASHTO M332-14.
[0126] Separation Test: ASTM D7173, Standard Practice for Determining the Tendency of Polymers to Separate from Polymer-Modified Bitumen.
[0127] Softening Point Test: ASTM D36, Standard Test Method for Softening Point of Asphalt (Ring-Ball Apparatus).
[0128] ABS (Difference (top - bottom)), ° C. Values less than or equal to 5 ° C. were considered to pass.
[0129] PG: Performance Grade, AASHTO M320, Standard Specification for Performance-Graded Asphalt Binders.
[0130] Table 3 shows five paving compositions comprising asphalt and linear low density polyethylene (LLDPE), wherein the LLDPE is a recycled plastic melted into the binder. The results show that when the LLDPE concentration is 2 wt% or greater (based on the total weight of the binder), the LLDPE and asphalt themselves are unstable, as shown by the ABS difference (top to bottom), wherein LLDPE concentrations above 2 wt% have a top to bottom softening point difference of greater than 5°C. In addition, at concentrations less than 2 wt%, the Brookfield viscosity and RTFO residual values are too low. Therefore, in an exemplary embodiment, the binder can be substantially free of LLDPE, such as having a concentration of about 1 wt% or less, or about 0.5 wt% or less, or about 0.1 wt% or less in various embodiments. However, combinations of LLDPE with other types of recycled plastics melted into the binder can produce viable products.
[0131] Table 3
[0132]
[0133]
[0134] Compositions are provided in weight %, based on the total weight of the binder composition.
[0135] Brookfield Viscosity: ASTM D4402, Standard Test Method for Viscosity of Bitumen at Elevated Temperatures Using a Rotational Viscometer.
[0136] G* (complex modulus), Δ (phase angle): According to ADTM D7175, Standard Test Method for Rheological Properties of Asphalt Binders Using Dynamic Shear Rheometer; G* / sin(Δ) can be calculated from G* and Δ. Values greater than or equal to 1.00 kilopascals (kPa) are considered passing values.
[0137] RTFO (Rolling Thin Film Oven) Test: ASTM D2872, Standard Test Method for Effects of Heat and Air on Moving Films of Asphalt (Rolling Thin Film Oven Test). Values greater than or equal to 2.20 kPa are considered a passing value.
[0138] MSCR (Multiple Stress Creep and Recovery) Test: ASTM D7405, Standard Test Method for Multiple Stress Creep and Recovery (MSCR) of Asphalt Binders Using a Dynamic Shear Rheometer.
[0139] R3.2: Average recovery rate at 3.2 kPa.
[0140] Jnr3.2: Irreversible creep compliance at 3.2 kPa. Values less than or equal to 4.50 kPa are considered pass values at both 70°C and 76°C.
[0141] Jnr diff: The difference between the irrecoverable creep compliance of 0.100 kPa and 3.200 kPa.
[0142] Multiple Stress Creep Recovery (MSCR) testing, using the method described in AASHTO T350-14 and the specifications in AASHTO M332-14.
[0143] Separation Test: ASTM D7173, Standard Practice for Determining the Tendency of Polymers to Separate from Polymer-Modified Bitumen.
[0144] Softening Point Test: ASTM D36, Standard Test Method for Softening Point of Asphalt (Ring-Ball Apparatus).
[0145] ABS (Difference (top - bottom)), ° C. Values less than or equal to 5 ° C. were considered to pass.
[0146] PG: Performance Grade, AASHTO M320, Standard Specification for Performance-Graded Asphalt Binders.
[0147] Table 4 shows 9 paving compositions that demonstrate the benefits of using waste plastics to replace mineral aggregates with or without low molecular weight oxidized polyethylene homopolymers. Aggregate gradients and mix designs are as described above and shown in these tables. "Control" is a typical gradient and mix design with 100% mineral aggregates. For Run #1 and Run #2, the commonly used large-size (20mm, 10mm and 6.3mm) mineral aggregates are replaced with an equal volume of waste high-density polyethylene pellets (5mm to 6mm). In these mixtures, fine aggregates, waste high-density polyethylene aggregates and fillers are heated at 120°C for 2 hours, and then the required amount of asphalt is added to the mixture, which is mixed with the help of a trowel until the entire mixture becomes uniform (approximately 20 minutes). For Run #3 and Run #4, the commonly used 20mm size mineral aggregates and half of the commonly used 10mm size mineral aggregates are replaced with an equal volume of waste high-density polyethylene pellets (5mm to 6mm). The remaining 10 mm, 6.3 mm aggregates, waste high density polyethylene aggregates and mineral aggregates of fillers were heated at 120°C for 2 hours and then the required amount of asphalt was added to the mixture, which was mixed with the help of a trowel until the entire mixture became uniform (about 20 minutes). In Run #7 and Run #8, the 6.3 mm aggregates were replaced with an equal volume of waste high density polyethylene pellets (5 mm to 6 mm). The 20 mm, 10 mm aggregates, waste high density polyethylene aggregates and mineral aggregates of fillers were heated at 120°C for 2 hours and then the required amount of asphalt was added to the mixture, which was mixed with the help of a trowel until the entire mixture became uniform (about 20 minutes). In Run #9 and Run #10, the 10 mm aggregates were replaced with an equal volume of waste high density polyethylene pellets (5 mm to 6 mm). The 20 mm, 6.3 mm aggregates, waste high density polyethylene aggregates and mineral aggregates of fillers were heated at 120°C for 2 hours and then required amount of bitumen was added to the mixture which was mixed with the help of trowel until the entire mixture became homogeneous (about 20 minutes).
[0148] All asphalt mixes were compacted 75 times on both sides using a Marshall compactor. All paving compositions containing waste plastic pellets as aggregates had lower densities than the "control" paving compositions, which will contribute to the production of lighter weight building materials with a number of benefits, including: 1) less load requirements on the base layer supporting paving materials prepared with these paving compositions; and 2) less fuel consumption when transporting paving materials prepared with these paving compositions. In addition, because the mineral aggregates were replaced on a volume basis with waste plastic pellets, and the mineral aggregates had a much higher density, the amount of asphalt used for the runs using waste plastic was much less than that used for the controls. Overall, the reduction in asphalt (the most expensive material in the control paving composition) ranged from 38% (no polyolefin) to 45% (polyolefin) for Run #1 and Run #2; from 17% (no polyolefin) to 25% (polyolefin) for Run #3 and Run #4; from 17% (no polyolefin) to 26% (polyolefin) for Run #7 and Run #8; and from 12% (no polyolefin) to 21% (polyolefin) for Run #9 and Run #10. Without being bound by theory, it is possible that waste plastic aggregates have a smaller porosity than mineral aggregates, and therefore asphalt that is typically absorbed into the pores of the mineral aggregates is not absorbed into the pores in the alternative waste plastic. Therefore, this asphalt that is not absorbed into the pores can be used to provide structure and functionality to the asphalt in the paving composition. Furthermore, even though the density of asphalt is lower and the amount is reduced for paving compositions containing waste plastic pellets as aggregate, the performance of paving compositions containing waste plastic is comparable to or even better than paving compositions containing all mineral aggregates, as indicated by the Marshall stability data.
[0149] The binder was the same for all runs, except that Run #2, Run #4, Run #8, and Run #10 included 2 wt% of a low molecular weight oxidized polyethylene homopolymer based on the weight of the asphalt, and Run #1, Run #3, Run #7, and Run #9 did not include any low molecular weight oxidized polyethylene homopolymer. Run #2, Run #4, Run #8, and Run #10 had higher density and higher Marshall stability than Run #1, Run #3, Run #7, and Run #9, respectively, which would improve the longevity of roads produced using asphalt blends containing low molecular weight oxidized polyethylene homopolymers. As can be seen in Run #2, Run #4, Run #8, and Run #10, the use of low molecular weight oxidized polyolefins produces paving compositions with better properties and reduced asphalt content.
[0150] Table 4, Part 1
[0151]
[0152]
[0153] Density is determined by ASTM D2726, Standard Test Method for Bulk Specific Gravity and Density of Nonabsorbent Compacted Asphalt Mixtures. Marshall Stability: ASTM D6927; Standard Test Method for Marshall Stability and Flow of Asphalt Mixtures.
[0154] Table 4, part 2
[0155]
[0156] Density is determined by ASTM D2726, Standard Test Method for Bulk Specific Gravity and Density of Nonabsorbent Compacted Asphalt Mixtures. Marshall Stability: ASTM D6927; Standard Test Method for Marshall Stability and Flow of Asphalt Mixtures.
[0157] The mix designs for Run #5 and Run #6 are provided in Table 5.
[0158] Table 5
[0159]
[0160] Table 6 shows the Marshall stability and voids filled with asphalt (VFB) for samples with and without low molecular weight oxidized polyethylene homopolymer used as a performance enhancing additive when the same mix design as in Table 5 is used.
[0161] Run #5 in Table 6 was prepared by heating coarse mineral aggregates (20 mm, 10 mm and 6.3 mm) at 150°C to 160°C for 2 hours and then adding the required amount of shredded waste plastic and low molecular weight oxidized polyethylene (LMWPE) to the heated aggregates to coat the aggregates. Fillers and fine aggregates were then added to the mixture and mixed until the temperature of the entire mixture was 150°C to 160°C. Asphalt was then added to the mixture at 160°C and mixed until the mixture was uniform. The mixture was then transferred to a Marshall mold and compacted 75 times on both sides using a Marshall compactor. Run #6 used the same method but without the LMWPE.
[0162] Table 6
[0163]
[0164]
[0165] LMWPE - low molecular weight oxidized polyethylene.
[0166] Stability: ASTM D6927; Standard Test Method for Marshall Stability and Flow of Asphalt Mixtures.
[0167] VFB (Voids Filled with Asphalt): ASTM D3203 / AASHTO &269; Standard Test Method for Percent of Air Voids in Compacted Dense and Open Asphalt Paving Mixtures.
[0168] Table 7 shows the test results when polyethylene terephthalate (PET) is used as the waste plastic. The "control" is a typical gradient and mix design with 100% mineral aggregates, as described and shown above. In Run #11 and Run #12, the 6.3 mm aggregates were replaced with an equal volume of waste PET pellets (5 mm to 6 mm). The mineral aggregates of 20 mm, 10 mm aggregates, waste PET aggregates and fillers were heated at 120°C for 2 hours, and then the required amount of asphalt was added to the mixture, which was mixed with the help of a trowel until the entire mixture became uniform (about 20 minutes). Like the above-mentioned waste high-density polyethylene waste plastics, waste PET plastics allow the use of less asphalt while having acceptable Marshall stability results. In addition, the use of low molecular weight oxidized polyethylene homopolymer in the binder allows for further reduction of asphalt and increases Marshall stability compared to Run #11 with the same amount of waste PET but without low molecular weight oxidized polyethylene homopolymer in the binder.
[0169] Table 7
[0170]
[0171]
[0172] Density is determined by ASTM D2726, Standard Test Method for Bulk Specific Gravity and Density of Nonabsorbent Compacted Asphalt Mixtures. Marshall Stability: ASTM D6927; Standard Test Method for Marshall Stability and Flow of Asphalt Mixtures.
[0173] Table 8 shows the test results when polystyrene (PS) is used as the waste plastic. The "control" is a typical gradient and mix design with 100% mineral aggregates, as described and shown above. In Run #13 and Run #14, the 6.3mm aggregates were replaced with an equal volume of waste PS pellets (5mm to 6mm). The mineral aggregates of 20mm, 10mm aggregates, waste PS aggregates and fillers were heated at 120°C for 2 hours, and then the required amount of asphalt was added to the mixture, which was mixed with the help of a trowel until the entire mixture became uniform (about 20 minutes). Like the above-mentioned waste high-density polyethylene plastics, waste PS plastics allow the use of less asphalt while having acceptable Marshall stability results. In addition, compared with Run #13 with the same amount of waste PS but without low molecular weight oxidized polyethylene homopolymer in the binder, the use of low molecular weight oxidized polyethylene homopolymer in the binder allows further reduction of asphalt and increases Marshall stability. When waste PS plastics are utilized, the use of low molecular weight oxidized polyethylene homopolymer in the binder increases Marshall stability very significantly.
[0174] Table 8
[0175]
[0176]
[0177] Density is determined by ASTM D2726, Standard Test Method for Bulk Specific Gravity and Density of Nonabsorbent Compacted Asphalt Mixtures. Marshall Stability: ASTM D6927; Standard Test Method for Marshall Stability and Flow of Asphalt Mixtures.
[0178] As can be seen from the examples, the use of low molecular weight oxidized polyethylene homopolymer allows the amount of asphalt in the paving composition to be reduced. By adding a low molecular weight oxidized polyethylene homopolymer in an amount of about 1 weight % to about 3 weight % based on the total weight of the binder, the amount of binder in the paving composition can be reduced to about 5.5 weight % of the paving composition or about 5.1 weight % of the paving composition, and still provide comparable performance relative to a comparable paving composition that does not contain the low molecular weight oxidized polyethylene homopolymer. The above examples also illustrate that waste plastics can be incorporated into the aggregate in an amount of about 1 weight % to at least about 13.5 weight % based on the total weight of the paving composition, and still provide an effective product. For example, the paving composition can include waste plastics in an amount of about 1 weight % to about 15 weight %, and still provide an effective product. In an exemplary embodiment, the waste plastics used as the aggregate may include one or more of high density polyethylene, polyethylene terephthalate and / or polystyrene.
[0179] Figures 1 to 4is a photograph of mineral aggregates combined with 10 wt % of waste plastic (based on the weight of the aggregates) covered with a binder. Figure 1 and Figure 2 In the invention, the binder is 100% by weight of asphalt. Figure 3 and Figure 4 In the present invention, 3 wt % of low molecular weight oxidized polyethylene is also added to the aggregate-waste plastic mixture based on the total weight of the binder. After the aggregate is heated at 150°C for 2 hours, 10 wt % of chopped waste plastic relative to the weight of the aggregate is added to the heated aggregate so that the chopped waste plastic effectively covers the surrounding of the aggregate. The low molecular weight oxidized polyethylene (if used) is then added to the aggregate-waste plastic mixture. Then, based on the total weight of the asphalt composition, 5 wt % of asphalt is heated to 160°C to obtain the desired fluidity, and it is added to the aggregate / chopped waste plastic / low molecular weight oxidized polyethylene composition and mixed to coat the aggregate with asphalt. Afterwards, the coated aggregate is equilibrated to room temperature, deionized water is then added, and it is kept in a water bath at 40°C for 24 hours. Figure 1 and Figure 3 Results are shown for samples without and with low molecular weight oxidized polyethylene. Figure 1 and Figure 3 show, Figure 1 The aggregates in the Figure 3 The aggregates in the concrete are completely covered with asphalt binder.
[0180] Two samples (#2 and #4) were evaluated in a boiling water test according to ASTM D3625, where the specimens were kept in boiling water for 10 minutes and then observed. Figure 2 and Figure 4 The aggregates without and with low molecular weight oxidized polyethylene after boiling water test are shown. Figure 2 and Figure 4 show, Figure 2 The aggregates in the Figure 4 The aggregates in the concrete are completely covered with bitumen.
[0181] These tests showed that the low molecular weight oxidized polyethylene increased the coverage of the aggregate by the binder compared to a binder without the low molecular weight oxidized polyethylene.
[0182] Although several embodiments have been presented in the foregoing detailed description, it should be understood that a large number of variations exist. It should also be understood that one or more embodiments are merely examples and are not intended to limit the scope, applicability, or configuration of the present disclosure in any way. On the contrary, the foregoing detailed description will provide a convenient guide for those skilled in the art to implement the various embodiments of the asphalt composition, it being understood that various changes may be made to the function and arrangement of the described elements without departing from the scope as set forth in the appended claims and their legal equivalents.
Claims
1. A paving composition, comprising: A binder, wherein the binder comprises asphalt, recycled plastic, and a performance enhancing additive, wherein the performance enhancing additive is selected from the group of low molecular weight polyolefins, glycidyl compounds, and combinations thereof, wherein the low molecular weight polyolefins have a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, wherein the glycidyl compound comprises ethylene glycidyl (meth)acrylate polymer, and wherein the ethylene glycidyl (meth)acrylate polymer has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons.
2. The paving composition of claim 1, wherein the paving composition comprises the binder in an amount of about 1 wt % to about 15 wt % based on the total weight of the paving composition; and The paving composition further comprises aggregates in an amount of about 85 wt % to about 99 wt % based on the total weight of the paving composition, wherein the aggregates are solid materials distinguishable from the binder by detection.
3. The paving composition of claim 2, wherein the aggregate comprises from about 1 wt% to 100 wt% waste plastics based on the total weight of the aggregate, and wherein the waste plastics comprise one or more of polystyrene, polyolefins, polyethylene terephthalate, polyvinyl chloride, polymers made from ethylene propylene diene monomers, ethylene vinyl acetate, polyesters, polytetrafluoroethylene, polyurethanes, polycarbonates, polyamides, polyacrylamides, and polymethacrylamides.
4. The paving composition of claim 2, wherein the paving composition comprises the binder in an amount of about 5.5 wt% or less based on the total weight of the paving composition.
5. The paving composition of claim 1, wherein the binder comprises the recycled plastic in an amount of about 1 wt% to about 20 wt%, based on the total weight of the binder.
6. The paving composition of claim 1, wherein the recycled plastic comprises about 90 wt% to 100 wt% polyethylene based on the total weight of the recycled plastic.
7. The paving composition of claim 1, wherein the low molecular weight polyolefin is selected from the group consisting of polyethylene, oxidized polyethylene having an acid value of about 5 mg KOH / gm to about 40 mg KOH / gm, polypropylene, thermally degraded wax, Fischer-Tropsch wax, and combinations thereof, and is present in the binder in an amount of 0.5 wt % to about 5 wt %, based on the total weight of the binder.
8. The paving composition of claim 1 , wherein the performance enhancing additive comprises a glycidyl compound in an amount of about 0.1 wt % to about 5 wt % based on the total weight of the binder, and wherein the paving composition further comprises polyphosphoric acid in an amount of about 0.1 wt % to about 1 wt % based on the total weight of the binder.
9. The paving composition of claim 1, wherein the recycled plastic comprises linear low density polyethylene in an amount of about 2 wt% to about 4 wt% based on the total weight of the binder, and wherein the performance enhancing additive comprises the glycidyl compound and the polyphosphoric acid.
10. The paving composition of claim 1, wherein the recycled plastic comprises high density polyethylene in an amount of 4 wt% to about 6 wt%, based on the total weight of the binder, and the performance enhancing additive comprises the glycidyl compound and the polyphosphoric acid.
11. A method for preparing a paving composition, the method comprising the steps of: preparing a binder comprising asphalt, a performance enhancing additive, and recycled plastic, wherein the performance enhancing additive is melted into the binder, wherein the performance enhancing additive is selected from the group of low molecular weight polyolefins, glycidyl compounds, and combinations thereof, wherein the low molecular weight polyolefins have a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, wherein the glycidyl compound comprises an ethylene (meth)acrylate glycidyl polymer having a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, and wherein the recycled plastic is melted into the binder; and The binder is mixed with aggregate to prepare the paving composition, wherein the aggregate is a solid material distinguishable from the binder by detection.
12. The method of claim 11, wherein the aggregates comprise from about 1 wt% to 100 wt% waste plastics based on the total weight of the aggregates, and wherein the waste plastics comprise one or more of polystyrene, polyolefins, polyvinyl chloride, polymers made from ethylene propylene diene monomers, ethylene vinyl acetate, polyesters, polytetrafluoroethylene, polyurethanes, polycarbonates, polyamides, polyacrylamides, and polymethacrylamides.
13. The method of claim 11, wherein the recycled plastic comprises low density polyethylene such that the binder comprises from about 4 wt% to about 8 wt% low density polyethylene based on the total weight of the binder.
14. The method of claim 11, wherein the performance enhancing additive is selected from the group consisting of low molecular weight polyethylene, low molecular weight oxidized polyethylene having an acid value of about 5 mg KOH / gm to about 40 mg KOH / gm, low molecular weight polypropylene, Fischer-Tropsch wax, thermally degraded wax, maleated polypropylene, maleated polyethylene, ethylene vinyl acetate, ethylene acrylic acid, glycidyl compounds, polyphosphoric acid, and combinations thereof, and wherein the performance enhancing additive is added to the binder in an amount of about 0.1 wt % to about 5 wt % based on the total weight of the binder.
15. The method of claim 11, wherein the adhesive has a top sample and a bottom sample, wherein the top sample and the bottom sample of the adhesive are provided by a separation test as described in ASTM D7173, and wherein the top sample softening point and the bottom sample softening point have a difference of less than 5°C as determined by a Ring and Ball softening point test, wherein the Ring and Ball softening point test is described by ASTM D36.
16. A paving composition, comprising: a binder in an amount of about 1 wt % to about 15 wt % based on the total weight of the paving composition, wherein the binder comprises asphalt; Aggregate, said aggregate in an amount of about 85 wt % to about 99 wt % based on said total weight of said paving composition, wherein said aggregate is a solid material distinguishable from said binder by detection, and wherein said aggregate comprises about 1 wt % to 100 wt % of waste plastic based on the total weight of said aggregate; and A performance enhancing additive, wherein the performance enhancing additive is selected from the group of a low molecular weight polyolefin, a glycidyl compound, and combinations thereof, wherein the low molecular weight polyolefin has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons, wherein the glycidyl compound comprises an ethylene glycidyl (meth)acrylate polymer, and wherein the ethylene glycidyl (meth)acrylate polymer has a weight average molecular weight of about 500 Daltons to about 30,000 Daltons.
17. The paving composition of claim 16, wherein the binder comprises recycled plastic in an amount of about 1 wt % to about 15 wt % based on the total weight of the binder, and wherein the recycled plastic comprises about 90 wt % to 100 wt % polyethylene based on the total weight of the recycled plastic.
18. The paving composition of claim 16, wherein the paving composition comprises the binder in an amount of about 5.5 wt% or less based on the total weight of the paving composition.
19. The paving composition of claim 16, wherein the low molecular weight polyolefin is selected from the group consisting of low molecular weight polyethylene, oxidized polyethylene having an acid value of about 5 mg KOH / gm to about 40 mg KOH / gm, polypropylene, thermally degraded wax, Fischer-Tropsch wax, maleated polyethylene, maleated polypropylene, ethylene vinyl acetate, ethylene acrylic acid, and combinations thereof, and is present in the binder in an amount of 0.5 wt % to about 5 wt %, based on the total weight of the binder.
20. The paving composition of claim 16, wherein the waste plastic comprises high density polyethylene, polyethylene terephthalate, polystyrene, or a combination thereof.